THE INFLUENCE OF PARENTAL SOCIAL STRATA ON THE JOINING PATTERNS OF GRADE V STUDENTS IN ISLAMIC ELEMENTARY SCHOOL - Nuruddin; Raudatul Jannah (El Midad, 2023)
Differences in the social strata of parents of students will of course also have different methods of educating children, high social strata have more established resources and better knowledge in educating their children, thus causing differences in the pattern of social interaction of children in social interaction at school. This study aims to determine the influence of parents' social strata on the social patterns of fifth-grade students at  Islam Darussalam elementary school in Gegerung Village, Lingsar District, West Lombok Regency. The type of research used is field research with a quantitative approach. Sampling was carried out using a census technique using 28 respondents as a sample. Data analysis methods used are validity tests, reliability tests, classic assumption tests, linear regression analyses, and hypothesis testing. The results of the research conducted show that first, the form of social strata of the parents of fifth-grade students at Islamic elementary school is a form of open social stratification. Second, the pattern of association of students at school is more personal communication, solidarity, and mutual cooperation are still strong because they come from the same ancestry. The social strata of parents have a significant effect on the social pattern of fifth-grade students.